The impact of participatory budgeting on health and wellbeing: a scoping review of evaluations - Mhairi Campbell; Oliver Escobar; Candida Fenton; Peter Craig (BMC, 2018)
Abstract Background Participatory budgeting (PB), citizens deliberating among themselves and with officials to decide how to allocate funds for public goods, has been increasingly implemented across Europe and worldwide. While PB is recommended as good practice by the World Bank and the United Nations, with potential to improve health and wellbeing, it is unclear what evaluations have been conducted on the impact of PB on health and wellbeing. Methods For this scoping review, we searched 21 databases with no restrictions on publication date or language. The search term 'participatory budget' was used as the relevant global label for the intervention of interest. Studies were included if they reported original analysis of health, social, political, or economic and budgetary outcomes of PB. We examined the study design, analysis, outcomes and location of included articles. Findings are reported narratively. Results From 1458 identified references, 37 studies were included. The majority of evaluations (n = 24) were of PB in South America, seven were in Europe. Most evaluations were case studies (n = 23) conducting ethnography and surveys, focussing on political outcomes such as participation in PB or impacts on political activities. All of the quantitative observational studies analysing population level data, except one in Russia, were conducted in South America. Conclusion Despite increasing interest in PB, evaluations applying robust methods to analyse health and wellbeing outcomes are scarce, particularly beyond Brazil. Therefore, implementation of PB schemes should be accompanied by rigorous qualitative and quantitative evaluation to identify impacts and the processes by which they are realised.